Insulin-like growth factor-1 prevents Aβ[25-35] / (H2O2)-induced apoptosis in lymphocytes by reciprocal NF-κB activation and p53 inhibition via PI3K-dependent pathway (2006)
ABSTRACT The role of insulin-like growth factor (IGF-1) as neural survival factor for the treatment of Alzheimer’s disease has recently gained attention. The present study shows that IGF-1 protects lymphocytes from (10, 30 mM) Ab[25–35] and (25, 50, 100mM) H2O2-induced apoptosis through NF-kB activation and p53 down regulation involving the phosphoinositide 3-kinase (PI-3K)–dependent pathway as demonstrated by using either (25 mM) LY294002 (PI-3K inhibitor), (10 nM) ammonium pyrrolidinedithiocarbamate (PDTC; NF-kB inhibitor), 50 nM pifithrin-a (PFT; p53 inhibitor) or by using immunocytochemistry detection of NF-kB and p53 transcription factors activation. Importantly, IGF-1, PDTC and PFT were able to protect and rescue lymphocytes pre-exposed to 10 mM Ab[25–35], even when the three compounds were added up-to 12 h post- Ab[25–35] exposure. Altogether these results suggest that survival/rescue of lymphocytes from Ab[25–35] toxicity is determined by p53 inactivation via IGF-1/ PI-3K pathway.